Activity of a vmPFC-DRN Pathway Corresponds With Resistance to Acute Social Defeat Stress - Grizzell, J. Alex; Clarity, Thomas T.; Graham, Nate B.; Dulka, Brooke N.; Cooper, Matthew A. (Frontiers in Neural Circuits, 2020)
The ventromedial prefrontal cortex (vmPFC) plays a critical role in stress resilience through top-down inhibition of key stress-sensitive limbic and hindbrain structures, including the dorsal raphe nucleus (DRN). In a model of experience-dependent stress resistance, socially dominant Syrian hamsters display fewer signs of anxiety following acute social defeat when compared to subordinate or control counterparts. Further, dominants activate vmPFC neurons to a greater degree during stress than do subordinates and become stress-vulnerable following pharmacological inhibition of the vmPFC. Dominants also display fewer stress-activated DRN neurons than subordinates do, suggesting that dominance experience gates activation of vmPFC neurons that inhibit the DRN during social defeat stress. To test whether social dominance alters stress-induced activity of a vmPFC-DRN pathway, we injected a retrograde tracer, cholera toxin B (CTB), into the DRN of dominant, subordinate, and control hamsters and used a dual-label immunohistochemical approach to identify vmPFC neurons co-labeled with CTB and the defeat-induced expression of an immediate early gene, cFos. Results indicate that dominant hamsters display more cFos+ and dual-labeled cells in layers V/VI of infralimbic and prelimbic subregions of the vmPFC compared to other animals. Furthermore, vmPFC-DRN activation corresponded directly with proactive behavioral strategies during defeat, which is indicative of stress resilience. Together, results suggest that recruiting the vmPFC-DRN pathway during acute stress corresponds with resistance to the effects of social defeat in dominant hamsters. Overall, these findings indicate that a monosynaptic vmPFC-DRN pathway can be engaged in an experience-dependent manner, which has implications for behavioral interventions aimed at alleviating stress-related psychopathologies.